A Simulation Study On Temperature Non-Uniformity Of Photovoltaic Thermal Using Computational Fluid Dynamics - Farhan, Irfan Alias (2021)
Energy generation from fossil fuels is the leading source of global greenhouse gas (GHG) emissions. With climate change being one of the biggest problems faced by modern society increasing energy supply by more production from fossil fuel would lead to quicker depletion of these resources and more pollution. To avoid the depletion of natural resources and to produce energy without harming the environment, renewable energy resources such as solar energy are being incentivized. PV technology utilizes solar energy to generate electricity and thermal energy. However, Photovoltaic (PV) cells operate at a lower efficiency at high operating temperatures. To enable the high-efficiency operation, photovoltaic thermal (PVT) systems are utilized. PVT aims to take the thermal energy away for PV cells and utilize it in other applications. The temperature distribution across the PV plate in most PVT systems is not uniform leading to regions of hotspots. The cells in these regions perform less efficiently leading to an overall lower efficiency of the PV plate. They can also be permanently damaged due to high thermal stresses. In this study, a custom absorber for a PVT is designed based on literature to provide a more even temperature distribution across the PV plate. The absorber design is tested via computational fluid dynamics (CFD) simulation using ANSYS Fluent 19.2 and the simulation model is validated by an experimental study with the percentage error in the range of 5.75% - 8.5%. The custom and the serpentine absorber utilized in the experiment are simulated under the same operating conditions having water as the working fluid. The custom absorber design is found to have a more uniform temperature distribution on more areas of the PV plate as compared to the absorber design utilized in the experiment, which leads to a lower average surface temperature of the PV plate. This results in an increase in thermal and electrical efficiency of the PV plate by 3.21% and 0.65% respectively. The new absorber is also tested at various mass flow rates and solar irradiance levels to understand the effect of said parameters on the performance and temperature uniformity of the PVT system. The new absorber design has an estimated thermal and electrical efficiency of 49.46% and 13.87%, respectively at 30 kg/h and 1000